European Digital Television: Future Regulatory Dilemmas - Näränen, Pertti (Javnost-The Public, 2002)
The development of digital television (DTV) has encountered many problems in the Europe. The recent collapse of terrestrial digital channels in Spain and UK, financial problems of even major satellite players and slow or stagnated user interest in most European countries demonstrate only one part of the difficulties. The combination of technological determinism, market optimism and inconsistent "light touch" regulation in the EU has accelerated the early development in Europe of digital television, but it has not been able to guarantee sound development in the long run. One of the major problems has been the standardisation. Industry led standardisation successfully developed the common digital transmission standards but the implementation of common "middleware" standards needed for interactive services and pay-TV access has not succeeded. Different standards are further segmenting European digital television markets. The development of European digital television is dominated by a few satellite broadcasters whose proprietary standards are preventing viewers from accessing a full range of digital channels with one device, thus causing unnecessary costs and delays both in the use and production of interactive DTV services. At the same time there is a constant threat of media concentration and competition problems. This chapter deals with past failures and future challenges and dilemmas in the European regulation of digital television development. Along with problems in standardisation, it discusses other policy dilemmas connected to DTV, like interactive advertising, the Listed Events policy and the remit of public regulation in general.